'Are you in a band?!': Participatory music-making in music teacher education. Issue 1 (1st March 2015) - Randles, Clint; Griffis, Sarah-Anne; Ruiz, Jose Valentino
This article is the account of a music teacher educator, a doctoral student (teaching assistant) and a pre-service music teacher regarding the impact that an innovative course offering at a large research university in the south-eastern United States had on students' perceptions of their musicianship and notions of what a music teacher is and does. Elements of Tom Turino's participatory music-making, hi-fidelity and studio audio art (in addition to presentational music-making) were infused into a new course sequence. Students formed independently operated small groups and worked on original arrangements of popular music selections and original songs for both live performance and recording. Pre-service music teachers' developing musicianship and notions of what a music teacher is and does were impacted. While the scope of the class and complimentary lab class incorporated all of the areas of music-making that Turino details in his work, this piece will focus on the incorporation of participatory music-making into music teacher education. The authors would also like to bring the work of Keith Sawyer into the conversation surrounding participatory music-making that includes elements of improvisation.